Physical, Emotional, and Sexual Violence on the Risk of Depression in Young Adult Women - Ayu Saidah; Argyo Demartoto; Bhisma Murti; Achmad Arman Subijanto; Revi Gamma Hatta Novika (Masters Program in Public Health, 2025)
Background: Depression due to dating violence is a serious problem that affects the mental health of many women, especially young adults. Dating violence, whether physical, emotional, or sexual, can interfere with psychological well-being and result in long-term consequences, one of which is depression. This study aims to analyze the relationship between experiences of dating violence and depression in victims, focusing on women aged 16 to 25 years.Subjects and Method: This study was a cross-sectional study conducted in Surakarta from October to December 2024. The study sample consisted of 200 female young adults in Surakarta City, selected through random sampling. The dependent variable was depression., Independent variables were physical violence, emotional violence, and sexual violence. Data were collected using questionnaires and analyzed using path analysis on Stata 13.Results: The risk of depression was directly influenced by emotional violence (b=0.49; 95%CI=0.39 to 0.60; p<0.001) and sexual violence (b=0.21; 95%CI=0.09 to 0.32; p<0.001). Meanwhile, the indirect influence was physical violence (b=0.28; 95%CI=0.15 to 0.41; p<0.001) and sexual violence (b=0.25; 95%CI=0.11 to 0.37; p<0.001).Conclusion: Emotional violence and sexual violence directly affect the risk of depression. The indirect influence of the risk of depression is physical violence and sexual violence.